Laser cladding of FeCrMoCB metallic glass on nickel-free stainless-steel to develop durable and cost-effective biomedical implants / Mahmoud Zakaria Alsayed Abdalfattah Ibrahim - Mahmoud Zakaria Alsayed, Abdalfattah Ibrahim (2019)
Medical implants are man-made devices used to treat, heal or recover living tissues problems or deficiencies. The market surveys predicted that the global market value of medical implants will hit 116 billion USD by 2022. The orthopedic or bone implants segment is leading with 31% share of the total medical market and the joint replacement represent most of this segment. These figures reveal the high potential of the orthopedic implants industry, especially, the joint replacement implants. Thus, numerous of researchers focused on developing biomaterials for joint replacement applications. To ensure durability and long-term implant, the applied biomaterial should prove high wear and corrosion resistance, suitable mechanical properties and acceptable biocompatibility. Currently, three major metallic alloys are used; Titanium alloy (Ti6Al4V), Cobalt alloy (CoCrMo), and 316L stainless-steel. However, Ti6Al4V alloy lacks the tribology properties, while the CoCrMo alloy and 316L stainless-steel fail to prove high biocompatibility in the long-term. Although the progressive advancement in biomaterials, there is no record for successful permanent or long-term implant. 316L stainless-steel is still used because it is cheaper than other alloys (about tenth the cost of Ti and Co-alloys) and approved by the US Food and Drug Administration (FDA) for temporary implants. Nickel ion release is considered one of the hazardous effect rising from the 316L stainless-steel. In a way to improve the biocompatibility of 316L stainless-steel, a nickel-free stainless-steel is proposed known as ASTM F2229 or Cronidur30. This proposed alloy not only improved the 316L stainless-steel biocompatibility excluding the Nickel ion hazardous effects but also proved better mechanical properties, enhanced wear and corrosion resistance. However, the alloy still needs further investigations to enhance its tribological, mechanical and biomedical characteristics to ensure the long-term durability for orthopedic implants. For this purpose, a cost-effective and durable Fe-based (FeCrMoCB) metallic glass is proposed to be laser cladded on ASTM F2229. Metallic glasses are featured with superior wear and corrosion resistance, mechanical properties and excellent biocompatibility. Fe-based metallic glass is abundant, available and has high glass forming ability. Laser cladding is a promising coating technique due to its ability to deposit vast materials on metals, establish a real metallurgical bond, thus high strength adhesion between the coating layer and the substrate, rapid heating and cooling rate required for amorphous structure formation, and offer clean and controllable technique. The cladded samples were prepared by preplacing FeCrMoCB amorphous powder on 30x30x3 mm ASTM F2229 samples, then cladded using high power diode laser. To optimize the coating layer; laser power, scanning speed, substrate surface roughness, overlap percentage, and laser beam spot size were varied. The macro and microstructure were examined using Optical microscope and scanning electron microscope, respectively. While, the phase transformation was recognized and analyzed using X-ray diffraction. The hardness, wear behavior (dry and in simulated body fluid), and corrosion resistance, were evaluated by microhardness and nano-indentation, ball-on disk wear test, electrochemical polarization, respectively. The cytocompatibility and bioactivity were investigated using direct cell-culture test and soaking in simulated body fluid, respectively. The investigations showed that the studied variables affected significantly the amorphous structure of the cladded FeCrMoCB layer which in turn affected the mechanical, tribology and corrosion properties. The results showed that an amorphous-crystalline composite structure (76% amorphous content) showed better tribological properties than high amorphous structure (87% amorphous content). The cladded FeCrMoCB metallic glass layer proved higher hardness up to five times the substrate hardness, lower wear rate – both dry and wet – up to tenth that of the substrate, significantly enhanced corrosion resistance, beside good cytocompatibility. In addition, FeCrMoCB metallic glass showed excellent bioactivity which promotes it as intermediate bioactive material for excellent osseointegration in orthopaedic implants. It is concluded that the proposed FeCrMoCB metallic glass coating has high potential for bone implants, especially for joint replacement with higher durability and bioactivity and thus less revision surgeries is needed.